2005
DOI: 10.4049/jimmunol.175.4.2191
|View full text |Cite
|
Sign up to set email alerts
|

A Role for IL-27 in Early Regulation of Th1 Differentiation

Abstract: IL-27 is a novel IL-6/IL-12 family cytokine that is considered to play a role in Th1 differentiation, whereas the exact role of IL-27 in Th1 differentiation and its molecular mechanism remain unclear. In this study we demonstrate a role for IL-27 in the early regulation of Th1 differentiation and its possible molecular mechanism. The ability of IL-27 to induce Th1 differentiation was most prominent under Th1-polarizing conditions, but without IL-12 in a STAT4- and IFN-γ-independent manner, and was overruled by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
126
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 171 publications
(139 citation statements)
references
References 39 publications
(53 reference statements)
13
126
0
Order By: Relevance
“…In addition, IL-27-induced STAT3 activation was mediated through four Tyr residues in the YXXQ motif of the cytoplasmic region of gp130 as in the case of IL-6 (38). These results are consistent with our previous results using STAT1-deficient mice, showing that STAT1 activation is important for IL-27-induced augmentation of Th1 differentiation but not for IL-27-induced cell proliferation (6,8).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…In addition, IL-27-induced STAT3 activation was mediated through four Tyr residues in the YXXQ motif of the cytoplasmic region of gp130 as in the case of IL-6 (38). These results are consistent with our previous results using STAT1-deficient mice, showing that STAT1 activation is important for IL-27-induced augmentation of Th1 differentiation but not for IL-27-induced cell proliferation (6,8).…”
Section: Discussionsupporting
confidence: 83%
“…We recently demonstrated that IL-27 differentiates naive CD4 ϩ T cells into Th1 cells under Th1 polarizing conditions but without IL-12 via two distinct pathways. One is to rapidly up-regulate ICAM-1 expression followed by ERK1/2 activation through ICAM-1/LFA-1 interaction (8), and the other is to augment T-bet expression through p38 MAPK activation (9). Several previous studies using mice lacking one of the IL-27R subunits, T cell cytokine receptor (10)/ WSX-1 (11), revealed that IL-27 plays multiple roles including positive and negative regulation of immune responses (12,13).…”
Section: Stat3 Is Indispensable To Il-27-mediated Cell Proliferation mentioning
confidence: 99%
See 2 more Smart Citations
“…IL-27 exerts both proinflammatory and suppressive effects on T cells, augmenting Th1 polarization by the induction of T-bet and increasing expression of ICAM-1 and responsiveness to IL-12 (4,(8)(9)(10)(11)(12)(13), and suppressing CD4 + T cell proliferation and effector function, for example, via suppressor of cytokine signaling 3-dependent downregulation of CD28-mediated IL-2 production (14,15) or downregulation of the RORc/IL-17 pathway (16)(17)(18)(19). IL-27 also promotes the production of IL-10 by various effector CD4 + T cell populations, including Th1 and Th2 cells and CD4 + T cells polarized under Th17-inducing conditions (20)(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%